The Correlation of Community Knowledge Level of Makassar Citizens About Covid-19 and Compliance with The Use of Mask - Sahabuddin, Rosdiana; Ananta, M. Muhlis; Kusuma Hapsari, Bramantyas; Febriza, Ami (Sean Institute, 2022)
Acute Respiratory Syndrome caused by a virus that is a subtype of the SARS-CoV virus is called Covid-19 (SARS-CoV-2). This virus targets the respiratory system and results in COVID-19, an illness (Coronavirus Disease-2019). In addition, several other clinical signs of this illness are frequently seen, such as fever, anosmia, coughing, sore throat, or dyspnea. According to information from the Makassar City Health Office, as of August 1, 2021, there are 4310 current cases in Makassar City, with a downward trend in mask use. Aim: This study aims to determine whether there is a correlation between the amount of community knowledge about COVID-19 and the amount of mask compliance in Gunung Sari Village, Makassar. Methods: The study used observational analytical research with a cross-sectional design sample of 52 people. The sampling used a random sampling technique. Results: About 61.5% of respondents know about COVID-19 awareness. Among them, 21.8 % (7 respondents) rarely use masks, 31.2% (10 respondents) sometimes use a mask, and 46.9% (15 respondents) continuously use a mask. Furthermore, there was a statistical association between the level of knowledge about COVID-19 and compliance using a mask (p <0.05). Conclusions: It can be concluded that there is a significant correlation between community knowledge about Covid-19 awareness and mask compliance in Gunung Sari Sub-district